School improvement through government agencies: loose or tight coupling? - Bush, Tony (SAGE Publications, 2016)
In seeking to improve student outcomes, governments may choose to exercise direct control over schools, as in many centralised systems, or to provide frameworks for intermediate bodies to engage in improvement activities. One such body is the National College for School Leadership (NCSL), now the National College for Teaching and Leadership (NCTL) in England. The Department of Education of the South African province of Gauteng (GDE) has also chosen to implement its school improvement programmes partly through two specialist units, the Sci-Bono Discovery Centre, which focuses on maths, science and technology (MST), and the Matthew Goniwe School of Leadership and Governance (MGSLG), which specialises in school leadership, management, governance and teacher development. The purpose of this article is to report on an evaluation of the work of these two bodies, commissioned by the GDE as part of its 20th anniversary commemorations, through an analysis of relevant documents and interviews with 11 key actors in the operation of these specialist bodies. The article adopts loose coupling as its theoretical framework.